URINE GLUCOSE DETECTION AS A DIABETES DISEASE IN WOMEN AND ELDERLY IN KEDUNGPANDAN VILLAGE, JABON, SIDOARJO - Andreas Putro Ragil Santoso; Devyana Dyah Wulandari (UNUSA Press, 2021)
Diabetes is a disease of metabolic disorders caused by poor production of insulin by the pancreas or due to the use of body insulin which is not maximal, causing interference. The main diabetes that often occurs in the community is type 1 and type 2 diabetes because of the influence of body insulin. Examination for detection is intended so that the public can find out about the presence of glucose in the urine so that the community can immediately recover faster, considering that if there is a glucose level in the urine, there is an increase in the level of glucose in the blood. The method used in this community service is to collect residents at the center, which is then carried out by examining the urine sample using a urine dysptic. Based on the results of examinations carried out on 62 people consisting of mothers and the elderly, it showed that there were 10 positive people or 19% of the total sample. This shows that early detection is important because there are still people who do not know the importance of early detection of disease in themselves, especially in the Kedung Pandan area.